Development of emotional intelligence of primary school pupils - Broslavska , H.; Drygach, T. (Scientific notes of the pedagogical department, 2020)
Analyzing scientific research, we found the problem of little knowledge of the nature and elements of emotional intelligence of children of primary school age, the directions of its formation. The authors want to reveal the ways of solving this problem, which is complex, contradictory and at the same time relevant and in demand in modern psychological and pedagogical science, more widely in their article. They associate the presence of emotional intelligence of a person with various habits, work, happy moments in life, etc. The less attention a person pays to the development of their own emotional intelligence, the more time he/she will need to settle their own and others’ emotions (delight, sadness, joy, irritation, feelings, etc.). In the article: the concept of emotional intelligence, which occupies one of the most important places in human life (it is connected with various spheres of their activity, work, well-being, habits, etc.), is considered; reveals the nature and elements of children’s emotional intelligence, which appears and develops in primary school age. The authors analyzed methods favorable for the formation of primary school pupils’ emotional intelligence, its impact on the behavior of a child, and the increase in academic performance. The relationship between the development of primary school children’s emotional intelligence and such concepts as socialization, communication, adaptation has been established. Primary school teachers should pay attention to the formation of children’s various emotions. Awareness by teachers of the importance of schoolchildren’s emotional intelligence contributes to the focus of their educational activities. After all, each emotion is a manifestation of a certain behavior; implementation of actions; gestures and words with the help of which each person can explain their behavior and actions. In the article: the need to develop primary school students’ emotional intelligence for effective teamwork, successful cooperation, awareness of common interests, discovery of talents, motivation for cooperation, erudition is analyzed; it is noted that during the educational process the intellectual development of children takes place, the improvement of significant personal qualities of a person (independence, hard work, etc.).